1958
DOI: 10.1002/hlca.19580410420
|View full text |Cite
|
Sign up to set email alerts
|

Synthesen auf dem Phenothiazin‐Gebiet. 2. Mitteilung. N‐substituierte Mercaptophenothiazin‐Derivate

Abstract: The synthesis of a series of pharmacologically interesting N‐substituted derivatives of 3‐mercaptophenothiazines is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1968
1968
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…The neurophysiological and biochemical mechanisms underlying the actions of the phenothiazines are poorly understood (3). The clinical and pharmacological properties of thioridazine (a phenothiazine) were investigated by Bourquin et al (4) and by Taeschler and Cerletti (5). It has an insignificant anti‐emetic and extrapyramidal syndrome‐producing action (6).…”
Section: Discussionmentioning
confidence: 99%
“…The neurophysiological and biochemical mechanisms underlying the actions of the phenothiazines are poorly understood (3). The clinical and pharmacological properties of thioridazine (a phenothiazine) were investigated by Bourquin et al (4) and by Taeschler and Cerletti (5). It has an insignificant anti‐emetic and extrapyramidal syndrome‐producing action (6).…”
Section: Discussionmentioning
confidence: 99%
“…There are only a couple of published procedures for the preparation of enantiomers of thioridazine. [30][31][32] Bourquin et al reported the first synthesis of 1, starting from racemic piperidine alcohol 5 (Scheme 1). Enantiomers of 1 were separated via chiral resolution employing di-p-tolyl-L-tartaric acid as a chiral derivatizing agent, making this a rather inefficient synthesis of the desired enantiomer.…”
Section: Letter Syn Openmentioning
confidence: 99%
“…A round-bottomed flask was charged with Pd-catalyst: Pd 2 (dba) 3 or Pd(OAc) 2 (5-7.5 mol%), ligand: XPhos (10-15 2-ol 12 (10), secondary amine, base: NaO t Bu or Cs 2 CO 3 , and dry toluene (5 mL). The flask was flushed with argon for 5 min.…”
Section: General Procedures For Preparation Of 1-(2-amino)-5-oxido-10hmentioning
confidence: 99%
“…6 Among the effective compounds that proved to inhibit resistance, some phenothiazine derivatives were found of high activity. 7 With some of the most important such compounds involving chloropromazine 8 , trifluoperazine 9 , thioridazine 10 , two common structural features of these compounds should be pointed out: (i) presence of an alkyl chain attached to the nitrogen atom of the phenothiazine ring; (ii) presence of an amino moiety in most of the derivatives.…”
Section: Introductionmentioning
confidence: 99%